Description of the female of Allocosa yurae (Strand, 1908) (Araneae: Lycosidae, Allocosinae) - Brescovit, Antonio D.; Taucare-Rios, Andres (Zootaxa, 2013)
The genus Allocosa has a worldwide distribution with 139 described species and only 51 (36.7%) are known by both the sexes (Platnick 2013). Dondale and Redner (1983) reviewed the species of Allocosa from North and Central America, and stated that Allocosa is a New World genus. Three New World species, Allocosa tenebrosa (Thorell, 1897), A. danneili (Dahl, 1908) and A. yurae (Strand, 1908), were described based on immature specimens (Thorell 1897; Dahl 1908, Strand 1908). For A. yurae, the adult male was described recently by Brescovit & Álvares (2011) from the type locality in Peru and along with A. orinus (Chamberlin, 1916), are the only two Allocosa species recorded from this country.